Childhood Sleep Functioning as a Developmental Precursor of Adolescent Adjustment Problems - Ksinan Jiskrova, Gabriela; Vazsonyi, Alexander T; Klánová, Jana; Dušek, Ladislav (Child psychiatry and human development, 2020)
Sleep has been linked to adjustment difficulties in both children and adolescents; yet little is known about the long-term impact of childhood sleep on subsequent development. This study tested whether childhood sleep problems, sleep quantity, and chronotype predicted internalizing and externalizing problems during adolescence. Latent Growth Modeling using the Czech portion of the European Longitudinal Study of Pregnancy and Childhood (N = 4393) was utilized to test the developmental trajectories of sleep characteristics (from 1.5 to 7 years) as predictors of adjustment problems trajectories (from 11 to 18 years). Findings provided evidence that children with higher levels of sleep problems at 1.5 years (and throughout childhood) reported higher levels of internalizing and externalizing problems at age 11. Additionally, greater eveningness at age 1.5 predicted a greater increase in externalizing problems from ages 11 to 18 years. The results emphasize the importance of childhood sleep problems in evaluating the risk of future adjustment difficulties.
Keywords: Female; Infant; dítě; předškolní dítě; poruchy přizpůsobení; ženské pohlaví; longitudinální studie; Adolescent; lidé; těhotenství; Risk Factors; spánek; Male; kojenec; Child, Preschool; Sleep; rizikové faktory; Child; mužské pohlaví; Pregnancy; Adjustment Disorders; mladiství; Longitudinal Studies; Humans